1998
DOI: 10.1002/(sici)1096-9128(199809/11)10:11/13<1043::aid-cpe413>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Towards seamless computing and metacomputing in Java

Abstract: Due to its platform‐independent execution model, its support for networking, multithreading and mobile code, Java has given hope that easy Internet‐wide high‐performance network computing was at hand. Numerous attempts have then been made at providing a framework for the development of such metacomputing applications. Unfortunately, none of them addresses seamless sequential, multithreaded and distributed computing, i.e. the execution of the same application on a multiprocessor shared‐memory machine as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(42 citation statements)
references
References 10 publications
0
40
0
2
Order By: Relevance
“…Java// (ProActive) [2] is a 100% Java library for seamless crossparadigm high performance computing. Both environments are targeted towards high performance computing in pure Java.…”
Section: Fig 3 Results Of the Performance Measurementsmentioning
confidence: 99%
“…Java// (ProActive) [2] is a 100% Java library for seamless crossparadigm high performance computing. Both environments are targeted towards high performance computing in pure Java.…”
Section: Fig 3 Results Of the Performance Measurementsmentioning
confidence: 99%
“…They utilize special entities in the language itself or OS to implement concurrent computing, such as Thread class in Java and process or thread in Windows OS. Other research has shown how to implement active objects using normal OOPLs to benefit concurrent programming [CKV98,LS96]. In [LS96], active object is a behavioral pattern with multiple participants, such as Proxy, Scheduler, Servant etc.…”
Section: A Class May Be Designated As Active (Ie Each Of Its Instamentioning
confidence: 99%
“…Just like VM-based runtime-MOPs, Proxy-based runtime MOPs such as RJava [9] or ProActive [5], reify things that only exist at runtime, like object creation or method calls. The difference is that proxy-based runtime-MOPs are targeted at the standard Java runtime environment and do not rely on a specialized VM.…”
Section: Proxy-based Runtime Mopsmentioning
confidence: 99%